VIRTUAL ETHNOGRAPHY OF @DAILYHOTELS.ID ACCOUNT AS A HOTEL PROMOTION MEDIA IN INDONESIA - Shafa, Aliyya Sausan; Achmad, Zainal Abidin (JARES (Journal of Academic Research and Sciences), 2024)
Content management is planning and managing content uploaded on social media that can support promotional activities. This study aims to understand content management strategies to help promotional activities by the @dailyhotels.id account. This study uses a qualitative method with a virtual ethnographic approach. Data collection in this study used virtual searches and interviews with six informants: one account owner @dailyhotels.id, one admin @dailyhotels.id, and four followers @dailyhotels.id. The results of the study show that the content management strategy can help the process of promotional activities for hotels in Indonesia by @dailyhotels.id to have an impact on promotional activities and create purchasing decisions for potential customers. Furthermore, @dailyhotels.id conducts content management to support promotional activities by interacting with @dailyhotels.id followers. In this study, it can be concluded that the content management strategy can help the promotion process be effective and convey information about hotels that the public does not know widely.